PENGARUH NILAI PELANGGAN DAN KEPUASAN PELANGGAN TERHADAP LOYALITAS PELANGGAN PADA SERVIS KENDARAAN DI PT. AGUNG AUTOMALL HARAPAN RAYA PEKANBARU - Wetri Efita (JURNAL EKONOMI BISNIS DAN MANAJEMEN, 2023)
This study aims to determine the effect of customer value and customer satisfaction on customer loyalty in vehicle servicing at PT. Agung Automall Harapan Raya Pekanbaru. The sample of this research is 99 people. The data technique used is multiple linear regression using SPPS 24. Based on the results, customer value has a positive effect on customer loyalty in vehicle servicing at PT. Agung Automall Harapan Raya Pekanbaru. And customer satisfaction has a positive effect on customer loyalty in vehicle servicing at PT. Agung Automall Harapan Raya Pekanbaru. There is a significant influence between customer value and customer satisfaction simultaneously or jointly on customer loyalty in vehicle servicing at PT. Agung Automall Harapan Raya Pekanbaru. R Square of 0.631 or 63.1%, this means that 63.1% of the customer loyalty variable can be explained or influenced by customer value and customer satisfaction at PT. Agung Automall Harapan Raya Pekanbaru